2021
DOI: 10.15586/aei.v49i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of asthma in Mexican children and adults with a positive rtRT-PCR test for SARS-CoV-2: a cross-sectional study during the 2020 pandemic

Abstract: Background: It has recently been argued that asthma does not increase the risk of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. If so, the prevalence of asthma in subjects diagnosed with COVID-19 should be lower than in the general population. Objective: To determine the prevalence of asthma in Mexican children and adults with SARS-CoV-2 infection.Methods: A public database of the Epidemiological Surveillance System for Viral Respiratory Disease in Mexico was analyzed. Those who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…A nationwide cohort of 219,959 South Korean adults reported a slightly higher risk of testing positive for SARS-CoV-2 among individuals with asthma, 16 while a study of 400,000 children and adults in Mexico reported a lower prevalence of individuals with asthma among those testing positive for SARS-CoV-2. 17 Moreover, studies of pediatric populations have not identified an increased risk of SARS-CoV-2 infection among children with asthma. A retrospective, single-site EHR-based study in the United States of 7,256 children tested for SARS-CoV-2 found that the asthma prevalence among children who tested positive for the virus was approximately the same as the overall pediatric asthma prevalence among children in the network.…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide cohort of 219,959 South Korean adults reported a slightly higher risk of testing positive for SARS-CoV-2 among individuals with asthma, 16 while a study of 400,000 children and adults in Mexico reported a lower prevalence of individuals with asthma among those testing positive for SARS-CoV-2. 17 Moreover, studies of pediatric populations have not identified an increased risk of SARS-CoV-2 infection among children with asthma. A retrospective, single-site EHR-based study in the United States of 7,256 children tested for SARS-CoV-2 found that the asthma prevalence among children who tested positive for the virus was approximately the same as the overall pediatric asthma prevalence among children in the network.…”
Section: Discussionmentioning
confidence: 99%
“…Almost 2 years have passed since the start of the SARS-CoV-2 pandemic, and the relationship between asthma and COVID-19 remains inconsistent because while recent studies have shown that asthmatics have a reduction in the risk of acquiring CO-VID-19 6,8,9 , others, as in the case of this research, have found the opposite. Although it would be difficult to have a clear answer to this dilemma through a survey, it should be noted that many of the investigations which have documented a lack of association, or a "protective" association between asthma and COVID-19, were conducted in the general population, while HW have characteristics or conditions that differentiate them from the rest.…”
Section: Discussionmentioning
confidence: 55%
“…The most-recent meta-analysis included almost one million patients with COVID-19, and the overall prevalence of asthma was estimated at 8.1% 8 . A cross-sectional study conducted in Mexico showed that the prevalence of asthma in adults with COVID-19 was 3.3% 9 .…”
Section: Discussionmentioning
confidence: 99%
“…We identified female sex, airborne allergy, and smoking to be associated with protection from Covid‐19, which is in line with previous findings. A Spanish registry study covering close to half a million individuals showed that the risk of contracting Covid‐19 was lower in asthmatics with an odds ratio of 0.74 (95% CI: 0.71–0.77) [ 24 ]. Although it is clear that smoking is a risk factor for the severity of Covid‐19, early studies reported an underrepresentation of smokers among patients hospitalized for Covid‐19 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%